The Resource Management Strategy of Nazir and Religious Instructors in Empowering Waqf Potential at the Religious Affairs Office (KUA) of East Binjai District - Muhammad Fahrul Rozy; Muhammad Nur Iqbal (SEAN Institute, 2026)
This study discusses the role of nazhir and religious instructors and strategies for strengthening both in empowering the potential of waqf at the Office of Religious Affairs (KUA) of East Binjai District. Waqf is an Islamic economic instrument that has great potential in improving community welfare if managed professionally and productively. However, waqf management in East Binjai District still faces various obstacles, such as low public understanding of productive waqf, suboptimal management of waqf assets, and limited human resource competency in waqf management. This study aims to determine the role of nazhir in waqf management, the role of religious instructors in raising public awareness about waqf, and strategies for strengthening the role of nazhir and religious instructors in empowering the potential of waqf at the KUA of East Binjai District. The research method used is a qualitative method with a descriptive approach. Research data were obtained through observation, interviews, documentation, and literature studies related to waqf and its empowerment. The results show that nazhir has an important role in the administration, management, development, and protection of waqf assets so that they can be used productively for the benefit of the community. Meanwhile, religious instructors act as educators, motivators, facilitators, and community mentors to increase public understanding and participation in productive waqf. Strengthening strategies include improving the quality of human resources through training and coaching, public outreach on productive waqf, improving the administration and legality of waqf assets, strengthening inter-institutional cooperation, and utilizing information technology in waqf management. .